KINERJA GURU MATEMATIKA BERDASARKAN PERSEPSI DAN KOMPETENSI SISWA SMP DI KOTA MERAUKE - Nur’aini, Khumaeroh Dwi; Ruslau, Maria F V. (Journal of Honai Math, 2020)
This study aims to evaluate the strengths and weaknesses of teachers in the teaching process in terms of aspects of mathematics teacher competency. It describes how the four teacher competencies have been running in the learning process in the classroom based on students' perceptions related to student competencies themselves using Structural Equation Modeling data analysis techniques (SEM). The study population was all junior high school students in Merauke City, Papua. The method of sampling was used proportional random sampling, which is continued by simple random sampling, to obtain a total sample of 436 students. The data collection was carried out by distributing questionnaires to students' perceptions about the performance of mathematics teachers consisting of 48 questions in the form of a Likert scale. The results obtained that pedagogic and social competencies are competencies that affect student competencies with mathematics teacher pedagogical competence is most influential on student competencies. Therefore, to improve student competency, teachers need to improve pedagogical and social competence.